History of Location Objectives (Hilal Tracker): Development of Astronomical Observations from 2015-Present - Marataon Ritonga; Alya Fathi Muhammad Hasibuan; Rizqan Arya Perdana Nazara (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2025)
This study examined the development of Hilal Tracker as a system for determining the location of hilal observations that has been developed since 2015 until now. This system emerged from the need for an accurate, efficient, and documented way to find the best place to see the Hilal, which is an important factor in determining the beginning of the month in the Hijri calendar. This article explains the history of the development of hilal Tracker technology and methods, including integrating astronomical data, using satellite imagery, algorithms for predicting hilal visibility, and cooperation with various local and international institutions. With a historical qualitative approach and chronological documentation, this paper examined the changes in innovation from the early phase to the modern stage. The findings showed that Hilal Tracker has improved the accuracy of rukyat location selection, strengthened the global hilal visibility database, and supported the alignment of hisab and rukyat methodologies in some Islamic countries. In addition, this system functions as a link between classical Islamic astronomy and modern technology through an open approach and academic collaboration. Therefore, Hilal Tracker is not just a technical device, but also a means of education and diplomacy in creating a unified Hijri calendar worldwide with an observational approach. This study recommends further development of local weather forecasting aspects and artificial intelligence to improve location efficiency in the future.